Teknik Era Bisu dalam Visualisasi Film The Artist - Agustinus Dwi Nugroho (Pascasarjana ISBI Bandung, 2019)
The focus of the study is on how the process of fi lmmaker in producing his works. Especially on the technology of silent fi lm to become the cinematic techniques in visualizing the present fi lms. Narratively, this study analyzes the small portion of the fi lm through coding system, namely, descriptive code and interpretative code in order to obtain the pa